Access the future of education : business [electronic resource] - Rice University; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Houston, TX Rice University, 1999)
Quoted from the homepage: Our open source textbooks are written by professional content developers who are experts in their fields. All textbooks meet standard scope and sequence requirements, making them seamlessly adaptable into existing courses. OpenStax textbooks undergo a rigorous peer review process. View the list of contributors when you click on each book.
University Library (UL)
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; Business -- Open educational resource -- Electronic book; Accounting -- Open educational resource -- Electronic book; Statistics -- Open educational resource -- Electronic book; Management -- Open educational resource -- Electronic book; Entrepreneurship -- Open educational resource -- Electronic book; Organizational behavior -- Open educational resource -- Electronic book; Business law -- Open educational resource -- Electronic book